A Diagnostic Algorithm That Combines Quantitative 18F-FDG PET Parameters and Contrast-Enhanced CT Improves Posttherapeutic Locoregional Restaging and Prognostication of Survival in Patients With Esophageal Cancer. (January 2019) - Tamandl, Dietmar; Fueger, Barbara; Haug, Alexander; Schmid, Rainer; Stift, Judith; Schoppmann, Sebastian F.; Ilhan-Mutlu, Aysegül; Ba-Ssalamah, Ahmed
Abstract : Purpose: The aim of this study was to determine whether the combination of contrast-enhanced CT (CE-CT) and quantitative 18 F-FDG PET parameters improves locoregional restaging in esophageal cancer (EC) after neoadjuvant therapy. Methods: Eighty-eight consecutive patients with locally advanced esophageal cancer, who underwent restaging after neoadjuvant chemotherapy or chemoradiotherapy before esophagectomy, were included in this retrospective study. The diagnostic accuracy of CE-CT, visual 18 F-FDG PET/CT (vPET/CT), and quantitative PET parameters was assessed for T and N staging. Histopathology was used as the reference standard. The prognostic value for recurrence-free survival, cancer-specific survival, and overall survival was assessed using Cox regression analysis. Results: Sensitivity, positive predictive value, and accuracy were 78.8%, 70.2%, and 59.0% (CE-CT), and 81.1%, 81.1%, and 68.2% (vPET/CT) for T staging as well as 59.5%, 75.9%, and 50.0% (CE-CT), and 70.2%, 93.7%, and 67.0% (vPET/CT) for N staging, respectively. Tumor length and metabolic tumor volume (MTV) exhibited an incremental increase with advancing T stages ( P = 0.002 and 0.038). Contrast-enhanced CT had the highest sensitivity to differentiate advanced T stages (T3/4 vs 0–2; area under the receiver operating curve [AUC], 0.86; P < 0.001), whereas MTV at a threshold of 5.8 mL had the highest sensitivity to detect complete response (T0 vs 1–4; AUC, 0.77; P = 0.002). Contrast-enhanced CT and MTV combined had an even superior accuracy to predict complete response (AUC, 0.82; P < 0.001). The imaging American Joint Committee on Cancer stage provided a better prognostication of recurrence-free survival, cancer-specific survival, and overall survival than either T stage, N stage derived from CE-CT or vPET/CT, or quantitative PET parameters alone. Conclusions: Combined CE-CT and MTV had the highest diagnostic accuracy to identify the posttherapeutic T stage, allowing for robust prediction of recurrence and survival. Abstract : Supplemental digital content is available in the text.